2020
DOI: 10.1002/tkm2.1270
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory effect of fermented brown rice and rice bran with Aspergillus oryzae on mice

Abstract: Aim In this study, we examined the anti‐inflammatory effect of fermented brown rice and rice bran with Aspergillus oryzae (FBRA) on acute and chronic inflammation mouse models. Methods As an acute inflammation model, we used a 12‐O‐tetradecanoylphorbol‐13‐acetate (TPA)‐induced ear edema model. As a chronic inflammation model, we used an imiquimod (IMQ)‐induced psoriasis model and ragweed pollen‐induced allergic rhinitis model. We also investigated the effect of FBRA on the expression of inflammatory mediators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Additionally, an experimental animal study reported that the administration of fermented brown rice was able to reduce the mRNA expression of several indicators of inflammation. 11 Meanwhile, an in vitro study, reported that the special protein content in brown rice was able to provide an inflammatory-reducing effect as well as the effect of selenium. 12 Further studies are needed to truly optimize the health benefits of eating brown rice especially by patients with type 2 diabetes mellitus.…”
Section: Significance For Public Healthmentioning
confidence: 99%
“…Additionally, an experimental animal study reported that the administration of fermented brown rice was able to reduce the mRNA expression of several indicators of inflammation. 11 Meanwhile, an in vitro study, reported that the special protein content in brown rice was able to provide an inflammatory-reducing effect as well as the effect of selenium. 12 Further studies are needed to truly optimize the health benefits of eating brown rice especially by patients with type 2 diabetes mellitus.…”
Section: Significance For Public Healthmentioning
confidence: 99%
“…This evidence underscores the anti-inflammatory attributes of fermented brown rice, highlighting its potential as a natural anti-cancer resource. Furthermore, fermented brown rice with Aspergillus oryzae has been found to have anti-inflammatory effects in skin irritation and allergic rhinitis scenarios [31]. It was imperative to acknowledge that while these findings are promising, many were derived from in vitro experiments or animal models.…”
Section: Significant Comparison Of the Anti-cancer And Anti-inflammat...mentioning
confidence: 99%
“…Economically and environmentally, brown rice offers more benefits than white rice [24]. This is because the wheat grains are removed during the milling process to produce white rice, leading to a significant wastage of rice bran [28,31]. Moreover, fermented brown rice not only boosts nutritional value by altering rice's nutritional composition and increasing its beneficial content but also contains a substantial number of phenolic chemicals and plant polyphenols [1,7,11].…”
Section: Economic and Consumer-oriented Environmental Benefitsmentioning
confidence: 99%